Does Intermittent Energy Restriction Plus Mediterranean Diet Reduce Visceral Adipose Tissue and Minimize Adaptive Responses of Energy Restriction? A Randomized Pilot Study (P21-016-19). (13th June 2019) - Panizza, Chloe; Lim, Unhee; Yonemori, Kim; Cassel, Kevin; Wilkens, Lynne; Shvetsov, Yurii; Harvie, Michelle; Marchand, Loïc Le; Shepherd, John; Delp, Edward; Boushey, Carol
Abstract: Objectives: Test if an intermittent energy restriction with a Mediterranean diet (IER + MED) preferentially promotes loss of visceral adipose tissue (VAT) over subcutaneous adipose tissue (SAT), with minimal changes to resting energy expenditure (REE) and physical activity level (PAL), compared to an active control, the Dietary Approaches to Stop Hypertension (DASH) diet, in an East Asian adult population. Methods: Men and women in Hawai'i ( n = 60, aged 35–55, BMI 25–40, VAT ≥ 90cm 2 for men and ≥ 80cm 2 for women) of East Asian origin, were randomized equally to IER + MED (2 days with 70% energy restriction and 5 days euenergetic MED) or a 7 day euenergetic DASH diet for 12 weeks. Dual energy X-ray absorptiometry (DXA) for estimation of VAT and abdominal SAT, REE through indirect calorimetry, and physical activity questionnaires were collected at baseline and week 12. Four-days mobile food records were completed at baseline, weeks 5–6 and 11. Results: At week 12, participants in the IER + MED group lost greater amounts of VAT (−22.6 ± 3.6 cm 2 vs. −10.7 ± 3.5 cm 2 in DASH, P = 0.022) and SAT (−48.2 ± 6.4 cm 2 vs. −15.0 ± 6.1 cm 2 in DASH, P < 0.001). The IER + MED diet did not preferentially promote loss of VAT over SAT compared to DASH. Changes in VAT: SAT were 0.01 ± 0.01 for both groups (IER + MED vs. DASH, P = 0.825). Mean daily energy intake reductions at week 11 were larger in IER + MED (27%) than DASH (16%); and mean loss of weight at week 12 was higher in the IER + MED group (−5.9 ± 0.7 kg vs. −3.3 ± 0.6 kg in DASH, P = 0.007). Despite the significant drop in energy and weight for IER + MED, there was a non-significant change in REE of −105 ± 56 kcal/day for IER + MED ( P = 0.068) and −25 ± 57 kcal/day for DASH ( P = 0.663). Hours of moderate-to-vigorous physical activity per day were 1.6 ± 0.2 for IER + MED and 1.4 ± 0.3 for DASH at baseline and did not change significantly over 12 weeks. Conclusions: In this short-term pilot study, the IER + MED diet was more effective at reducing VAT, SAT and weight; however, it did not preferentially promote loss of VAT over SAT, as compared to the active control DASH group. Loss of VAT, SAT and weight from the IER + MED diet may be sustainable long term as REE and PAL, which commonly decrease with large energy restriction, did not significantly change over 12 weeks. Funding Sources: The William & Ellen Melohn Endowed Research Fund, University of Hawaii; National Institutes of Health, National Cancer Institute.